Perbedaan Kepuasan Mahasiswa Program Studi Manajemen dan Akuntansi Terhadap Implementasi Program Merdeka Belajar Kampus Merdeka (MBKM) Fakultas Ekonomi dan Bisnis Universitas Nusa Bangsa - Fitrianti, Dewi; Sukayat, Harmoko; Rumna; Widjadja, Ichwan Rachmanu (Jurnal EMT KITA, 2023)
The aim of the study was to find out the differences in student satisfaction in the Management and Accounting Study Program towards the Implementation of the Independent Campus Learning Program, Faculty of Economics, University of Nusa Bangsa. Data collection was carried out by direct observation, interviews, and questionnaires. Respondents' answers will be given an assessment score with a Likert scale. Methods of data analysis using descriptive qualitative. The object of research was students at Nusa Bangsa University at the Faculty of Economics and Business, a total of 142 respondents consisting of 99 students from the Management Study Program and 43 students from the Accounting Study Program. The results of the questionnaire were measured by the tangible, reliability, responsiveness, assurance, and empathy dimensions and used the Independent Samples t-test. Differences in satisfaction in the dimensions of reliability, responsiveness, assurance, and empathy for Management Study Program students are higher than for Accounting Study Program students. On the tangible dimension, Accounting Study Program students have a higher level of satisfaction than Management Study Program students. The results of the Independent Samples T Test on 5 dimensions obtained evidence that there was no difference in satisfaction between Management Study Program students and Accounting Study Program.